2016
DOI: 10.1371/journal.pone.0166096
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Analysis of Non-Measurable Enhancing Lesions Newly Appearing after Concomitant Chemoradiotherapy in Glioblastoma Patients for Prognosis Prediction

Abstract: PurposeTo analyze the enhancement patterns and apparent diffusion coefficient (ADC) values of non-measurable surgical cavity wall enhancement pattern, newly appearing after completion of standard concurrent chemoradiotherapy (CCRT) with temozolomide in glioblastoma patients for the prognosis prediction.Materials and MethodsFrom January 2010 to April 2014, among 190 patients with histopathologically confirmed glioblastoma, a total of 33 patients with non-measurable wall enhancement on post-CCRT MR imaging were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This phenomenon may be explained by the gliomas enrolled with lower grade in this study. The above mentioned MRI features could be detected more often in those post-treatment glioblastoma patients [12,13]. The incidences of thick-linear and nodular enhancement (34.87%), new distal enhancement (5.26%), new SVZ involvement (20.39%) were lower than those of glioma (51.52%, 25.43%, and 49.14% separately) [12,13].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This phenomenon may be explained by the gliomas enrolled with lower grade in this study. The above mentioned MRI features could be detected more often in those post-treatment glioblastoma patients [12,13]. The incidences of thick-linear and nodular enhancement (34.87%), new distal enhancement (5.26%), new SVZ involvement (20.39%) were lower than those of glioma (51.52%, 25.43%, and 49.14% separately) [12,13].…”
Section: Discussionmentioning
confidence: 85%
“…The conventional MR features analyzed included: the enhancement pattern of the residual cavity wall, new distal enhancement disease, new involvement of subventricular zone (SVZ). The enhancement of the residual cavity wall was categorized into three types: no enhancement; thinlinear enhancement (partial or entire wall enhancement with thickness < 3 mm), thick-linear (partial or entire wall enhancement of 3 ~ 5mm thickness) or nodular (5 ~ 10mm in thickness) enhancement [12]. New distal parenchymal enhancement was de ned as new enhanced disease that not contiguous (> 1.5 cm away from) with residual cavity or remnants of tumor after resection [13].…”
Section: Patientsmentioning
confidence: 99%
“…Previous studies using postoperative MR imaging have reported that thick or nodular enhancement patterns had a poorer prognosis than thin enhancements, according to a thickness criterion of 5 mm [24]. In addition, a recent study by Kim et al [28] of newly developed non-measurable enhancing lesions after CCRT reported a similar result, namely that the progression group showed frequent thick (≥ 3 mm) or nodular (≥ 5 mm) enhancements. Our current study differs from those of previous studies however because only thick wall enhancement (≥ 5 mm) was included in our present analysis to assess the significance of perfusion at SCWEs.…”
Section: Discussionmentioning
confidence: 88%
“…The imaging analysis and postprocessing were performed on a workstation (PHILIPS Extended MR WorkSpace 2.6.3.4). The enhancement patterns of residual cavity wall were divided into thin-linear (partial or entire wall enhancement with thickness <3 mm), thick-linear (partial or entire wall enhancement of 3–5 mm in thickness), and nodular wall enhancement (with nodular enhancement of 5–10 mm in thickness) patterns [ 14 ]. Cerebral blood volume (CBV) was calculated based on signal intensity-time curves in transverse T 2 ∗ -weighted sequence.…”
Section: Methodsmentioning
confidence: 99%